Direct and inverse problems for finite-dimensional perturbations of operators - Zolotarev, V. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
Spectral analysis of a self-adjoint operator, which is a finite-dimensional perturbation of the second derivative operator on a finite segment, is realized. The spectrum of this operator is described, and the inverse spectral problem is solved allowing us to find the corresponding perturbation from the n + 1 spectrum. Spectral data of the inverse problem are described.